Prevalence of chronic kidney disease and associated risk factors among people living with HIV in a rural population of Limpopo Province, South Africa - Choshi, Joel; Flepisi, Brian; Mabhida, Sihle E.; Sekgala, Machoene D.; Mokoena, Haskly; Nkambule, Bongani B.; Ndwandwe, Duduzile; Mchiza, Zandile J.; Nqebelele, Unati; Kengne, André P.; Dludla, Phiwayinkosi V.; Hanser, Sidney (Frontiers in Public Health, 2024)
Background: Limited evidence informs on the prevalence of chronic kidney disease (CKD) in people living with HIV (PLWH) in South Africa. Thus, this study aimed to determine the prevalence of CKD and its associated risk factors among PLWH within the rural province of Limpopo, South Africa.We conducted a cross-sectional study of 143 participants, sub-divided into groups of PLWH (n=103) and individuals without HIV (n=43). Structured questionnaires were used to collect and capture sociodemographic information including age, sex, alcohol intake, smoking status, and educational status. Basic measurements taken included levels of cluster of differentiation 4 (CD4+) count, body mass index (BMI), blood pressure, plasma cystatin C and fasting serum glucose levels. Plasma cystatin C-based estimated glomerular filtration rate (eGFR) was calculated using the chronic kidney disease epidemiology collaboration (CKD-EPI) estimator to determine CKD presence.The prevalence of CKD was approximately 7% in PLWH. Multivariate logistic regression analysis showed that it was only diabetes mellitus (odds ratio of 5.795, 95% confidence interval, p=0.034) and age (odds ratio of 1.078, 95% confidence interval, p=0.039) that were significantly associated with CKD in PLWH.Chronic kidney disease was prevalent in PLWH, and it was further associated with cardiovascular risk factors diabetes and ageing. As PLWH age, the burden of CKD may be increased with the increase in cardiovascularrelated comorbidities such as diabetes.